Students’ Acceptability of the START Approach as an Extension Tool - Bernardo, John V (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
In this study, the researcher determined the level of acceptability by students of the START Approach as utilized in a community extension. To do this, the researcher identified the attributes of the approach based on the literature and developed a survey questionnaire. The survey questionnaire was validated by experts in the field and was administered digitally to target respondents in January 2024. Salient findings showed that students rated the approach as highly acceptable in general, with a weighted mean of 3.57 in a scale of 4. The students claimed that the approach is flexible, practical, and doable, among other favorable attributes. Further, they claimed that the approach could be used to teach science investigatory projects. This pioneering approach has been developed as a potential extension tool with a wide range of areas of utilization even in fisheries research education.